Management of patients with cervical myelopathy - Gołębiowska, Natalia (Medical Studies/Studia Medyczne, 2019)
Myelopathy is a neurological deficit related to the spinal cord, and cervical spondylosis is its leading cause. The majority of middle-aged people have radiological evidence of significant cervical spine degeneration. The most characteristic symptoms are: neck pain with reduced range of motion, pain and paraesthesias in shoulders, gait disturbance, weakness or instability of lower extremities, loss of manual dexterity, and glove-distribution sensory loss in hands. The pathophysiology of cervical spondylotic myelopathy involves static, dynamic, and ischaemic factors. There are two surgical approaches: anterior and posterior. The posterior approach includes laminectomy and laminoplasty. The anterior approach includes anterior discectomy and fusion, and anterior corpectomy and fusion. This paper reviews the pathophysiology and clinical manifestation of cervical spondylotic myelopathy, and surgical approaches to treat patients with this disease.